Between documentality and imagination: Five theses on curating the violent past. (April 2018) - Bell, Vikki
This article considers the notion that to document or inscribe our lives not only leaves a trace of our creaturely presence, but may also become a form of juris-writing, a writing that concerns and aims at Justice. Employing an expanded notion of Justice that takes it beyond the institutions of law, therefore, it asks about forms of documentality (Ferraris) that put us 'before memory' in Derrida's sense. How is it possible to think curation in relation to a violent past in such a way that neither attempts to deny the lacunae nor surrenders in the face of the difficulties of such attempts? How should we consider the relation between the delimited encounter with an 'invitation to imagine' (Didi-Huberman) and processes of institutionalisation that build a society? What about those things that it is not possible to show, including relations of power, that arise analytically? Reflecting on current memory spaces, especially within ex-clandestine centres for detention, torture and extermination (ex-ccdtyes) in Argentina, the article offers five theses in order to consider what is at stake in the encounters staged at these sites.